RANS analysis of the self-propulsion performance for a twin-screw ship - Je-In Kim; Bu-Geun Paik; Jong-Woo Ahn; Il-Ryong Park (International Journal of Naval Architecture and Ocean Engineering, 2025)
This study presents a comprehensive estimation of full-scale self-propulsion performance for a high-speed, twin-screw, single-skeg surface vessel using Reynolds-averaged Navier–Stokes (RANS)-based computational fluid dynamics (CFD). Resistance, propeller open-water characteristics, and self-propulsion behavior were analyzed by incorporating recent benchmark data on surface roughness—identified as a critical factor in full-scale CFD analysis. The numerical predictions, including key self-propulsion parameters, were validated against full-scale performance data extrapolated from model tests conducted at KRISO. Additionally, ship speeds were estimated by simulating surge motion induced by thrust from specified propeller RPMs under wave conditions, replicating sea trial environments. Finally, ship speeds corresponding to the prescribed RPMs were compared across CFD simulations, model tests, and actual sea trial results.